THE INFLUENCE OF ENGLISH SOCIETY ON JANE AUSTEN'S EMMA: A SOCIOLOGICAL APPROACH - RUSSEDIYANI , DIAN PUSPA (2007)
This study elaborates people struggle in surviving their lives in the English society as depicted in Jane Austen's Emma, based on sociological approach. The aims of study are to expose Jane Austen's criticism against the domination of the upper class in the English society and to identify relation between the structure of Emma and the social condition of England in the late of eighteenth and early nineteenth century. This study belongs to a qualitative study. In the period, there are two types of data sources, which are used, namely primary and secondary data source. The primary data source. The primary data source and the object of the study is the novel Emma itself, meanwhile the secondary one is any literature related with this study. The writer collects the data from both, primary and secondary data source in a sort of document as evidence. The study uses the library research to collect the data. The collected data is analyzed by means of descriptive analysis. Having analyzed this novel, the conclusions are as follows; first, a literary work involves the response of the author toward the social realty where they live. Second, Jane Austen criticizes the condition at the time that was strongly dominated by the upper class. Third, the sociological analysis show the upper class of the social structure in the English society has dominated and exploited the classes below them. Jane Austen's criticism is her rationality to restructure the society and to build her ideal society.